Green extraction of curcuminoids from Zingiberaceae rhizomes using natural deep eutectic solvents: A systematic review - Utama, Niko (Universitas Muhammadiyah Magelang, 2025)
Curcuminoids are the main bioactive compounds found in the rhizomes of the Zingiberaceae family, particularly Curcuma longa, and are known for their significant pharmacological activities, such as antioxidant, antimicrobial, anti-inflammatory, and antimutagenic effects. Conventional extraction methods still rely heavily on toxic organic solvents that are environmentally unfriendly and have limited selectivity and efficiency. Natural Deep Eutectic Solvents (NADES), as green solvents composed of natural components such as choline chloride, organic acids, sugars, and alcohols, offer a more sustainable alternative. This systematic review evaluates the effectiveness of NADES for extracting curcuminoids from Zingiberaceae rhizomes, compares their performance with conventional solvents, and analyzes the influence of different extraction methods. Literature was retrieved from PubMed, ScienceDirect, and Google Scholar (2015”“2025), and 11 eligible articles were included in the analysis. The results show that combining NADES with energy-assisted extraction methods, such as microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE), yields high curcuminoid concentrations, with the highest reported yield reaching 89.87 mg/g using a choline chloride”“citric acid NADES. Locally sourced NADES formulations, such as nipa palm syrup and nipa vinegar, also demonstrated promising extraction performance. However, challenges remain regarding the high viscosity of NADES and the need for optimized extraction conditions. This study concludes that NADES are promising green solvents for extracting curcuminoids from Zingiberaceae rhizomes. The use of NADES not only enhances extraction efficiency and selectivity but also facilitates the development of environmentally friendly extraction technologies applicable to the functional food, cosmetic, and pharmaceutical industries.